(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted in the green house at Plant Protection Department/College of Agriculture-Abu Ghraib. Results shown the highest infestation rate of total Cucumber leaves Cucumis sativus was 40% leaf/plant in 17th of April, whereas the lowest was 6.7% in the 9th of February. Statistical analysis showed significant differences in LSD values. Results revealed the highest average of cucumber leaf miner Liriomyza bryoniae infested leaves reached 7 leaves/plant in the 17th of April when LSD values shown significant differences. The average number of tunnels per leaf was increased with the infestation developments when the average number of tunnels per leaf was 1.67 tunnel/leaf at the beginning of this study , then increased up to 9.67 tunnel /leaf at the mid of April. The infestation percentage by the leaf miner varied as well which was low at the beginning of sampling then increased gradually. The highest infestation percent was 32% in the 28nd of February while the lowest was 10% in the 9th of February. Results revealed two shapes of Leaf miner tunnels the zigzag-g and stain-shaped tunnels. The zigzag-shaped formation was higher than stain shape when scored 24 tunnels/leaf in the 17th of April while the lowest formation was 2 tunnels /leaf in the 19th of February. Whereas, the highest formation of stain-shaped tunnels was 14 tunnels/leaf in 7th of April and the lowest was 2 tunnels per leaf in the 9th of February. The parasitism of the following insects, attacking cucumber leaf miner, were reported Diglyphus crassinervis (Eulophidae)، Neochrysochairs Formosa (Eulophidae) (westwood,1833) وPediobius metalicus (Eulophidae).